Mengidentifikasi Kebutuhan Pengembangan Modul Ajar Apresiasi Puisi di SD - Elfa Rahmawati; Seni Apriliya; Anggit Merliana (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
Teaching modules by several educators in class IV elementary schools in poetry appreciation learning has not used a specific learning model. However, it still uses a general learning model. So this research was carried out to identify and analyze for teaching modules, then it will be developed into poetry appreciation learning in fourth grade elementary school. The method used is descriptive qualitative. The subjects in this research are educators and Indonesian teaching modules. The research was conducted in February-March 2024 at two elementary schools in Tasikmalaya City. Researchers collected data by carrying out observation, interviews and content analysis of teaching modules. Data analysis using the Miles and Huberman model involves three main stages: data reduction, data display, and drawing conclusions. The research results show that: (1) the components in the teaching module used are not in accordance with the components in the Badan Standar Kurikulum dan Asesmen Pendidikan Nomor 003/H/KR/2022; (2) there is no learning model specifically for learning poetry appreciation; and (3) in teaching poetry appreciation, educators have not yet aimed at appreciating the content of poetry. From the research results, it is necessary to develop a poetry appreciation teaching module using a special model. Therefore, researchers suggest that when creating teaching modules you should pay attention to the components in the teaching module, the learning model used, the material to be studied, and the needs required by students so that learning is in accordance with the objectives to be achieved and learning becomes more effective and efficient.